2011
DOI: 10.1103/physrevd.84.066004
|View full text |Cite
|
Sign up to set email alerts
|

Holography of charged black holes withRF2corrections

Abstract: We investigate several holographic properties of charged black holes with RF 2 corrections, which originate from Kaluza-Klein reductions of five-dimensional GaussBonnet gravity. We obtain the perturbative solution and discuss its thermodynamics. The DC conductivity is calculated via the effective action approach and the corrections to the DC conductivity are also evaluated. Moreover, we calculate the shear viscosity η and thermal conductivity κ T , as well as two interesting ratios η/s and κ T µ 2 /(ηT ). We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 47 publications
5
23
1
Order By: Relevance
“…In particular, the dependence of the result of [146] onα is correctly reproduced from the (neutral) five-dimensional η/s ratio. For non-zero charge, the answers differ since our solution is not a correction to the Reissner-Nordström black hole.…”
Section: Jhep09(2012)011mentioning
confidence: 62%
See 1 more Smart Citation
“…In particular, the dependence of the result of [146] onα is correctly reproduced from the (neutral) five-dimensional η/s ratio. For non-zero charge, the answers differ since our solution is not a correction to the Reissner-Nordström black hole.…”
Section: Jhep09(2012)011mentioning
confidence: 62%
“…One can compare our result (4.17) to that of [146], where a higher-order correction to the Reissner-Nordström black hole P λµνρ F λµ F νρ is considered for p = 3. Our result agrees with theirs in the zero charge limit, after matching conventions and defining an effective coupling for the gauge field g F = 2Le −φ/ √ 3 and an effective AdS radius L e = Le φ/2 √ 3 .…”
Section: Jhep09(2012)011mentioning
confidence: 90%
“…we consider a Maxwell field and a charged complex scalar field coupled in the background of a d -dimensional spacetime via the action [29,30] …”
Section: Superconductor Models With Rf 2 Correctionsmentioning
confidence: 99%
“…They argued that this correction term arises from the Kaluza-Klein reduction of five dimensional Gauss-Bonnet gravity and can produce second-order equations of motion for both the gauge field and metric in any general background [29]. Cai and Pang studied the holographic properties of charged black holes with RF 2 corrections and observed that this correction will affect the DC conductivity [30]. Considering this new form of higher derivative corrections, we wonder how the properties of the holographic superconductors will be modified.…”
Section: Introductionmentioning
confidence: 99%
“…This model helps in alleviating the fine tuning as well as cosmic coincidence problem (Urban and Zhitnitsky 2009a, 2009b, 2010a, 2010b, 2011Forbes and Zhitnitsky 2008). Several theoretical aspects have been investigated for this model (Ebrahimi and Sheykhi 2011;Sheykhi and Sadegh 2012;Sheykhi and Bagheri 2011;Rozas-Fernandez 2012;Karami and Fahimi 2013) and tested thorough different observational schemes (Cai et al 2011).…”
Section: Equation Of State Parametermentioning
confidence: 99%